Poverty Elevation by Islamic Finance - Rahma, Al Siddig Talha M. (European Journal of Applied Sciences, 2023)
This paper discuss the Islamic finance and its role to resolve poverty problems ,the different tools and models of Islamic finance will provide enriching of finance phenomena that emerge new era and changeable behavior, The paper also investigate the nature of traditional financing system that build upon the rate of interest model which only distributed the fund to high income groups. The paper focuses for these Islamic tools that diversification finance for, new methods of finance. Through mobilization of rural saving for poor people by providing financing for several potential areas including finance for agricultural inputs, agro-based industries ,milk plants, woolen mills, farm machinery assembly & rural structure projects. there by empirical investigation on the effect of Islamic finance as an alternative financial model to solve poverty alleviation problems have accomplished within the discussion, to result in showing why Islamic financial models are better as approach and practice than conventional one, , Islamic models can be implemented at the non-Moslem societies also.